A study of quality performance and deviations in public building in Bauchi State of Nigeria - Adegboyega Richard, Kolawole; Hadiza Dahiru, Bobbo; Raji Mohammed, Mudashir (International Journal of Engineering and Technology, 2019)
The construction industry occupies an important position in the Nigerian economy and contributes massively to her socio - economic improvement, while a building quality is one of the important measures of success in the construction industry. This essence of this Â paper is to evaluate the various factors affecting quality performance in public building construction projects; by comparing consultants and contractor perception of the factors affecting quality performance and to ascertain origins and scale of quality deviation in the design and construction phase of public building in Bauchi State. 125 questionnaires were administered to the study population through stratified random sampling technique, 64 consultants and 38 contractors responded indicating a response rate of 81.6%. Data were analyzed using Mean Item Score and Mann-Whitney U-test. The study identified: use of unskilled labour; poor on-site supervision; the experience and competence of supervising team as key variable affecting quality performance. The study indicated that there is no significant difference between consultant and contractors perceptions on the factors affecting quality performance in public building in Bauchi State and lastly by analyzing fifteen building construction projects files at completion the figures indicate that 83.05% of deviations had it root from design and 16.95% had it root from construction.Â Â Â